Farliga ämnen i Norrbottens län : En förstudie om förekomst och förmåga - Karlsson Sälgfors, Hanna (2011)
This report was conducted on behalf of the regional coordination function regarding hazardous substances. The report deals with the presence of hazardous substances at industrial facilities and on carriage by road and rail but also the municipal fire brigades and other relevant authorities' ability to manage accidents involving hazardous substances in the County of Norrbotten.Substances with hazardous properties are handled in large quantities. The carriage of hazardous substances are made by road, rail, sea and air. Transport by road is the most frequent way to carry dangerous goods on land. In Sweden severe incidents involving hazardous substances are rare but still occur each year. To minimize the risks of harm to people, environment and property the operation of hazardous substances are surrounded by laws and regulations. This framework is designed to minimize the risks involved in manufacturing, operations and transportation of hazardous substances.Because of the large-scale industries hazardous substances are handled extensively in Norrbotten. Large quantities of explosive and oxidizing substances are handled by the mining industry in the municipalities of Gällivare and Kiruna. Corrosive acids, bases and peroxides are handled in the paper pulp mills in Piteå and Kalix while large amounts of petroleum products are handled in the port of Luleå and Piteå, but also occurs throughout the country. To what extent, amount and frequency, hazardous substances are transported to, from and within the county by road is currently not defined. Because of this, carriage of all classes of dangerous goods can not be excluded to occur. Flammable liquids, oxidizing agents and flammable gases are the most frequent carriage of dangerous goods by rail. However, hazardous substances from almost all hazard classes, except radioactive materials, were carried by rail in 2010. The locations that are recipients or senders of dangerous goods is Piteå, Luleå, Haparanda, Gällivare and Kiruna where Luleå and Haparanda receiving and ...